Knowledge and Attitudes about Nutrition related to Snacking Practices in Madrasah Tsanawiyah Students - Lestari, Puji; Octavia, Zana Fitriana (Journal of Health Education, 2021)
Background: Snacks in students' social life are a means of socializing students with their friends. Students tend to consume less nutritious food. The practice of this student snack begins with the attitude of the students, which begins with the students' knowledge of nutrition. This study aims to analyze the relationship between knowledge and attitudes about nutrition on students' snacking practice. Methods: This study is a descriptive study with a cross-sectional research design. The research sample consisted of 133 students, who were students in grades 8 & 9 Mts Darul Ulum. Results: The results of the Spearman rho test, the relationship between nutritional knowledge and snacking practice (p = 0.084), the relationship between nutritional attitudes towards snacking practice (p = 0.013). Conclusion: Nutritional knowledge is not related to nutritional attitudes. Nutritional attitudes are related to snacking practices. KEYWORDS: Nutrition Knowledge; Snack Attitude; Snack Practices